Feasibility of sun and magnetic compass mechanisms in avian long-distance migration - Muheim, Rachel (Mov Ecol, 2018)
Birds use different compass mechanisms based on celestial (stars, sun, skylight polarization pattern) and geomagnetic cues for orientation. Yet, much remains to be understood how birds actually use these compass mechanisms on their long-distance migratory journeys. Here, we assess in more detail the consequences of using different sun and magnetic compass mechanisms for the resulting bird migration routes during both autumn and spring migration. First, we calculated predicted flight routes to determine which of the compasses mechanisms lead to realistic and feasible migration routes starting at different latitudes during autumn and spring migration. We then compared the adaptive values of the different compass mechanisms by calculating distance ratios in relation to the shortest possible trajectory for three populations of nocturnal passerine migrants: northern wheatear Oenanthe oenanthe, pied flycatcher Ficedula hypoleuca, and willow warbler Phylloscopus trochilus. Finally, we compared the predicted trajectories for different compass strategies with observed routes based on recent light-level geolocation tracking results for five individuals of northern wheatears migrating between Alaska and tropical Africa. We conclude that the feasibility of different compass routes varies greatly with latitude, migratory direction, migration season, and geographic location. Routes following a single compass course throughout the migratory journey are feasible for many bird populations, but the underlying compass mechanisms likely differ between populations. In many cases, however, the birds likely have to reorient once to a few times along the migration route and/or use map information to successfully reach their migratory destination. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s40462-018-0126-4) contains supplementary material, which is available to authorized users.